Individual Level of Predictors of Face to Face Bullying: The Findings of a Two-Wave Longitudinal Study - Bayraktar, Fatih (Nova Science Publishers, Inc., 2019)
Although the research on bullying is almost in its 50th year, still there is need for longitudinal studies. Therefore, the main purpose of this research was to examine the individual-level predictors of face to face bullying among a Turkish Cypriot adolescent sample in two waves (time interval: one year). A total of 268 adolescents (143 females, 124 males, 1 missing; Mean age = 14.7, SD = .52) have been recruited from public schools which settled in four different districts of Northern Cyprus. Age, gender, media use, perceived popularity vs unpopularity, prosocial and antisocial behaviors (both in real life and cyberspace) were analyzed as predictors in Time 1. Face to face bullying in Time 2 was predicted by face to face bullying, perceived unpopularity, age and using chat rooms in Time 1 positively. On the other hand gender (1 = female, 2 = male), helping others in cyberspace, perceived popularity and using blogs in Time 1 predicted face to face bullying negatively in Time 2. All coefficients were significant at p < .05. The results indicated that face to face bullying had a stability; older ones and females perpetrated bullying more; perceived unpopularity and using chat rooms were risks for future bullying. The findings will be discussed in both theoretical and practical implications. © 2019 by Nova Science Publishers, Inc.
Keywords: adolescents; face to face bullying; individual factors; longitudinal study; school